THE ROLE AND IMPORTANCE OF LEGAL ETHICS IN ADVOCACY PRACTICE (Multidisciplinary Journal of Science and Technology, 2025)
This article explores the fundamental role and importance of legal ethics in the professional practice of advocacy. It examines the key principles guiding lawyers’ conduct, including honesty, confidentiality, professional independence, and loyalty to clients. The article highlights ethical challenges commonly faced by lawyers, such as conflicts of interest and corruption, and emphasizes the need for a robust ethical framework within the legal profession. Comparative analysis with international practices, such as those of the CCBE and ABA, underscores the global standards for ethical legal conduct. In conclusion, the article provides actionable recommendations for strengthening legal ethics in Uzbekistan’s legal system.